Plasticized solid polymer electrolyte based on natural polymer blend incorporated with lithium perchlorate for electrical double-layer capacitor fabrication - Yusof, Yusliza; Shukur, M.F.; Hamsan, M.H.; Jumbri, Khairulazhar; Kadir, Mohd Fakhrul Zamani (Springer Verlag (Germany), 2019)
A plasticized solid polymer electrolyte system is prepared using polymer blend of methyl cellulose–potato starch with lithium perchlorate (LiClO4) as dopant salt and glycerol as plasticizer. Transport properties of the electrolytes are investigated using electrical impedance spectroscopy (EIS). By applying a method proposed by Arof et al. which was found to be suitable for both Arrhenius and Vogel–Tammann–Fulcher (VTF) type of electrolytes, the number density (n), diffusion coefficient (D), and mobility (μ) of ions are found to be influenced by the concentration of glycerol. From ion and electron transference number analysis, it is verified that ions are the main charge carriers. Linear sweep voltammetry (LSV) verifies the suitability of the most conductive electrolyte to be employed in the carbon-based symmetric electrical double-layer capacitor (EDLC) fabrication. The EDLC has been tested using the galvanostatic charge–discharge and cyclic voltammetry (CV) techniques. The specific capacitance (Csp) of the electrode using CV at a sweep rate of 2 mV s−1 is found to be 61.58 F g−1. The EDLC has been tested for 1000 charge–discharge cycles with the highest Csp value of 28.04 F g−1. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.